Law and Islamic finance: How legal origins affect Islamic finance development? - Rihab Grassa; Kaouthar Gazdar (Borsa Istanbul Review, 2014)
Many researchers have shown that differences in legal origin explain differences in financial development. Using historical comparisons and cross-country regressions for 30 countries observed for the period from 2005 to 2010, this study tried to assess if different legal origins impacted on the development of Islamic finance. More particularly, this paper tried to assess empirically why and how Shari'a Law's legal origins adopted wholly or partially (combined with Common or Civil Law) could explain the level of development of Islamic finance in different jurisdictions. Firstly, we found that countries adopting a Shari'a legal system had a very well developed Islamic financial system. Secondly, we found that countries, adopting a mixed legal system based on Common Law and Shari'a Law, were characterized by the flexibility of their legal systems to make changes to their laws in response to the changing socioeconomic conditions and that these helped the development of the Islamic financial industry. However, we found that countries, adopting a mixed legal system based on both Civil Law and Shari'a Law, were less flexible in making changes to their old laws and this thwarted the development of the Islamic financial industry in these countries. Thirdly, we found that the concentration of Muslim population (the percentage of Muslim population) had a positive effect on the development of the Islamic banking system. Also, the level of income had a positive and significant effect on the development of Islamic banking.